Formação inicial de coordenadores pedagógicos: concepções, identidade profissional e práticas pedagógicas - Araújo, Osmar Hélio Alves (2019)
The continuous training of basic education teachers in Brazil has often been applied in an insufficient and punctual manner, with implications for the promotion of productive learning and student permanence in school. This framework contributes significantly to the recognition that the professional constitution of pedagogical coordinators regarding their initial and continuing training, pedagogical knowledge and practices, as well as their role as teacher trainers, should be assessed in its broad dimensions. The study object of this research is the initial formation of pedagogical coordinators, applying as reference the construction of their professional identity and pedagogical practices. The research locus was the Ceará State High School Network - 5th Regional Coordination of Education Development - Tianguá (CE). General objective: to investigate initial pedagogical coordinator formation, applying as reference the construction of their professional identity and pedagogical practices, based on specialized literature on the subject and reflections of coordinators from the Ceará State High School, 5th CREDE - Tianguá - CE; specific objectives: to identify and analyse the profiles, focusing on initial and continuous training and experiences, that reveal the professionals that work in the pedagogical coordination of the Ceará State High School Network, 5th Crede - Tianguá - CE; to analyze coordinator conceptions from the Ceará State High School Network, 5th CREDE - Tianguá - CE; regarding their work as teacher trainers and their pedagogical practices. The research was developed in light of a qualitative approach and based on historical-dialectical materialism. Four education professionals occupying positions in a school coordinator commission were the subjects of this research. The research instrument consisted in a semi-structured interview and, regarding the data analysis, a content analysis from Bardin's (1977) perspective was carried out. This study revealed that pedagogical coordinators apply their theoretical-practical experiences, especially as teachers, to build their professional identity, pedagogical practices and work mediation as teacher trainers. Above all, it was considered, that the theoretical-practical elements concerning pedagogical coordination in their initial formation are sparsely explored and problematized